Development of Contextual Teaching and Learning Based on Flash Card Media in Grade IV Elementary School Science Learning - Jeni Ahmat Fahrezi; Satinem Satinem; Eka Lokaria (EDUJAVARE: International Journal of Educational Research, 2026)
Education functions as the main pillar in shaping the lives of human beings who are knowledgeable, characterful, and able to adapt to the times. This research aims to develop a product in the form of Flash Card learning media based on Contextual Teaching and Learning in the science subject of grade IV students that meets the criteria of valid, practical, and also effective. This research uses a research and development (R&D) approach with the ADDIE model which consists of five stages including the analysis, design, development, implementation, and evaluation stages. The product design process is done with the help of the Canva application which is customized based on the Learning Outcomes and Learning Objectives Flow of the Independent Curriculum. The results of this study are based on the results of validation tests conducted by 3 validators using Aiken's V calculations, showing the assessment of language validators of 0.93, media validators of 0.81, and material validators of 0.96, with a very valid category. As for the trial assessment of the practicality sheets of teachers and students, it was found that the Flash Card learning media based on Contextual Teaching and Learning has very practical criteria with an average score of 94.58%. Then for the effectiveness assessment trial involving 22 students in Class IV of SD Negeri 2 Rantau Bingin, an average N-Gain of 0.74 was obtained with a high category. Thus, it can be concluded that the data from the results show that Contextual Teaching and Learning-Based Flash Card learning media is very feasible and very practical to be used in the learning process of IPAS students in grade IV elementary school.